Pengalaman Hamil pada Usia Remaja: Studi Fenomenologi - Kusuma, Ratu (Jurnal Akademika Baiturrahim Jambi, 2024)
Riskesdas 2018 recorded 2,867 teenage pregnancies (10-19 years) and 15 of them were aged 10-14 years. BPS Indonesia reported that the average number of teenage births in Indonesia in 2018 was 36 births/1000 births, while in Jambi Province it was 46 births/1000 births. This means that the teenage birth rate in Jambi Province is very far from the national target, which is only births/1000 births. One of the highest contributing health centers is the Puskesmas Putri Ayu, where in the period 1-31 August 2022, 30 teenage pregnancies (16-19 years) were recorded. This study is qualitative research with a phenomenological approach to explore teenagers' experiences of adapting to pregnancy. Data collection was carried out from 08 December 2022 to 23 January 2023. The selection of participants was carried out using a purposive sampling technique of 7 teenage mothers. Data collection was carried out by means of triangulation (interviews, observations and documentation) which were recorded and recorded in field notes. Data analysis was carried out manually, without using an application. The research results found 9 themes related to the experience of pregnancy as a teenager, namely: 1) causes of marriage and pregnancy as a teenager; 2) physical complaints during pregnancy in adolescence; 3) perinatal complications; 4) psychological response due to pregnancy as a teenager; 5) family response and adverse impacts on the family; 6) husband's treatment after marriage; 7) views on new roles; 8) the response of society and health workers to the decision to marry and become pregnant during adolescence; and 9) coping in dealing with teenage pregnancy problems. It can be concluded that teenage pregnancy is caused by various factors and has various negative impacts.